FROM KNOWLEDGE TO ACTION: EMPOWERING INDONESIAN MIGRANT WORKERS THROUGH FINANCIAL LITERACY - Krissanya, Nofriska; Mahfirah, Titis Fatarina; Handaru, Agung Wahyu; Zakaria, Adam; Ahmad, Gatot Nazir; Anggraini, Ratna; Kurniaty, Kurniaty; Amirah, Aisyah (International Journal of Engagement and Empowerment (IJE2), 2024)
This article presents a community service initiative aimed at enhancing the financial literacy and entrepreneurial skills of Indonesian migrant workers in Malaysia, contributing to the Sustainable Development Goals (SDGs) of No Poverty (SDG 1) and Quality Education (SDG 4). Migrant workers often face significant barriers, including limited financial literacy and access to entrepreneurial opportunities, which hinder their socioeconomic advancement. The initiative, executed through a webinar titled "Unlocking Success: Financial Literacy & Entrepreneurial Empowerment", provided essential knowledge on personal financial management, entrepreneurial opportunities, and personal branding. The webinar featured expert speakers from Universiti Teknologi Mara Malaysia and Universitas Negeri Jakarta (UNJ). The event's success was reflected in positive participant feedback, although suggestions for future improvements included extended speaker interaction, language support, and alternative scheduling. The initiative underscores the importance of targeted interventions to empower migrant workers, enabling them to overcome socioeconomic challenges and contribute to sustainable development